Prevalence of cardiometabolic risk factors among Malaysian obese adults - Shahadan, Siti Zuhaidah; Daud, Azlina; Md Isa, Muhammad Lokman; Draman, Samsul; Ibrahim, Muhammad (International Islamic University Malaysia (IIUM), 2016)
Obese adults are associated with increased cardiometabolic risk (CMR). The study aims to investigate the prevalence of CMR factor abnormalities in obese adults in Kuantan. Methods: Seventy-six obese adults with a mean (standard deviation) age of 33.7 years (9.8 years) participated in this study. All participants had a waist circumference (WC) measured, blood pressure (BP) taken, and assessment of fasting blood glucose (FBG), lipid profile (LP) and high-sensitivity C-reactive protein (hs-CRP) level. Results: For CMR factors, the mean values for WC was 97.2 ± 9.6 cm, mean overall BP was 119 ± 15/76 ± 11 mmHg, mean FBG level was 4.8 ± 0.5 mmol/L and the mean of total cholesterol (TC) and triglyceride (TG) was 5.4 ± 1.0 mmol/L and 1.4 ± 0.7 mmol/L, respectively. Lastly, the mean of hs-CRP was 6.0 ± 6.1 mg/L. The CMR factors with the highest prevalence of abnormal values included WC (male 100%; female 98%) and TC (male 73.1%; female 52%) for both genders, systolic BP (50%) and TG level (61.5%) for male, and hs-CRP level (68%) for female. Out of the nine CMR factors measured, five CMR risk factors were shown to have a high prevalence of abnormalities. Conclusions: The present study suggests that obese adults in Kuantan have multiple CMR factor abnormalities. A larger trial, sensibly informed of this trial, can now build upon and confirm these results.